Flexible solid-state Li-ion battery using Ge thin film anode and LiCoO2 cathode - Vieira, E. M. F. (2015)
Flexible and solid – state Li-ion bat-teries (LIBs) can offer flexibility, lightweight and easy portability in large-scale energy storage, with significantly higher power and long cycle life. The anode is a crucial component affecting the perfor-mance of LIBs. Here, we investigate the electrochem-ical performance of e-beam deposited Ge anode (300 nm thick) coupled with LiCoO2/LiPON (cath-ode/solid-state electrolyte) in a microbattery system fabricated only by PVD techniques. LiCoO2 cathode was deposited by rf-sputtering with 120 W of power source and 17/3 sccm of Ar/O2, respectively. The LIPON was also deposited by rf-sputtering at 100 W of RF power. Microstructure and battery perfor-mance were investigated by scanning electron mi-croscopy (SEM) and electrochemical measurements (open circuit potential (OCP), charge/discharge cycles and electrochemical impedance spectroscopy (EIS).